Analisis Persepsi Kemudahan Penggunaan, Kenyamanan, Manfaat Dan Kepercayaan Yang Mempengaruhi Minat Menggunakan Bsi Mobile Palopo - Megasari Megasari; Nila Kartika Putri (IAIN Palopo, 2021)
This study aims to analyze the perceptions that determine customer interest in using BSI Mobile at Bank Syariah Indonesia. This type of research is a descriptive quantitative study with a population of all customers using BSI Mobile at BSI KCP Palopo Ratulangi with a sample of 201 respondents using the slovin formula. The data analysis technique used is multiple linear regression with hypothesis testing using the t test, F test and the coefficient of determination test (R2). The results of data analysis with the t test show that partially the variables perceived ease of use (X1), perceived convenience (X2), perceived benefits (X3) and perceived trust (X4) have a significant effect on customer interest (Y) using BSI Mobile at BSI KCP Palopo Ratulangi. This can be seen from the perceived ease of use (X1) with a tcount (4.947) > ttable (1.972) and a probability value of 0.000 <0.05; perceived comfort (X2) with a tcount (3.123) > ttable (1.972) and a probability value of 0.002 <0.05; perceived usefulness (X3) with a tcount (2.538) > ttable (1.972) and a probability value of 0.002 <0.05; and perceptions of trust with tcount (3,850) > ttable (1,972). The results of the F test also show that the four perception variables simultaneously influence customer interest in using BSI Mobile with a probability value of 0.000 <0.05. Meanwhile, the coefficient of determination (R2) of 0.479 indicates that 47.9% of variations in customer interest in using BSI Mobile can be explained by perceptions of ease of use, convenience, benefits and trust, while the remaining 52.1% is explained by other variables not examined in this study.